Artificial Intelligence in Project Management: Enhancing Efficiency and Decision-Making - Dr. Md. Mahfuzul Islam Shamim (International Journal of Management Information Systems and Data Science, 2024)
This thesis explores the integration of Artificial Intelligence (AI) in project management practices to improve efficiency and decision-making processes. As organizations increasingly rely on project management methodologies to execute tasks, deliverables, and achieve objectives, the role of AI in enhancing these processes becomes pivotal. Through an examination of existing literature, case studies, and theoretical frameworks, this thesis investigates the potential benefits, challenges, and implications of incorporating AI technologies in project management. It aims to provide insights into how AI can optimize project planning, scheduling, resource allocation, risk management, and stakeholder communication. Additionally, the thesis explores the ethical considerations and societal impacts associated with the adoption of AI in project management. By analyzing real-world applications and theoretical perspectives, this research contributes to the understanding of how AI can be effectively utilized to streamline project management practices and drive organizational success in diverse industries.